Teaching ethos in narrative autobiographical techno: embodiment, reframing and self reflection image of themselves in teacher vie rÃcits - Janicleide Vidal Maia (2016)
The new world order, called Technocracy (XAVIER, 2009) indicates that the school can not ignore the reality in which it operates, it is constituent of a communications transformation process promoted by new technologies, but incidents also in ways of working , to decide, to think. Given this and new pedagogical framework, we aim therefore investigate the constitution of the discursive ethos anchored in three aspects of autobiographical narratives, namely the report of the teaching pedagogical praxis - front postmodern contextual influence and adequacy challenge to current educational environment in the clinical interview (MAIA-VASCONCELOS, 2005), the redefinition of the self-image of the teachers vie ârÃcitâ and narrative self-receptivity. The research corpus is composed of 20 techno autobiographical narratives. The research rhetoric composition has a multidisciplinary theoretical approach, which includes studies in the areas of education, sociology, philosophy and linguistics, under different axes, namely: the studies of autobiographical narratives, as a research method, data analysis and formation of narrative (BOLÃVAR, DOMINGO e FERNÃNDEZ, 2001; DOMINICÃ, 2007; PASSEGI, 2011; BERTAUX, 2010; BRUNER, 2006; JOSSO, 2009; LEJEUNE, [2008] 2014; MAIA-VASCONCELOS, 2003; PINEAU e LE GRAND, 2012; BAKHTHIN, 2003); studies of the self-image in speech (AMOSSY, 2005), the biographical embodiment (JOSSO, 2007, 2008, 2012); the sensitive body (BOIS e RUGIRA, 2006; HUMPICH, 2008); the discursive ethos (MAINGUENEAU, 1995, 2006, 2011); technological habitus (BOURDIEU, 2002, 2003, 2004; BOURDIEU e CHARTIER, 2012; ALBUQUERQUE, 2005); the relationship between the foreshadowing, figuration and refiguration narrative (RICOEUR, 1994, 1995, 1997, 2000a, 2000b, 2011); the approaches to the post-modern educational context and the new pedagogy (UNESCO, 2005, 2008; DEMO, 2009; FINO, 2008; LIBÃNEO, 1998; CAHRLOT, 2008; KENSKY, 2012, 2013); the relationship between time and reflexivity (GIDDENS, 2002); the postmodern historical context (BALMAN, 2001). The analysis has revealed that teachers show be aware that, in addition to expertise in their area, must show, in particular, digital skills (CARENZIO, 2012). Therefore, the survey results allow us to say that the teachers ethos emerges in techno autobiographical narrative in the unveiling of a discursive game in which the narrative setting signifies that, interwoven by a dialectical relationship, in the same proportion that the pedagogical praxis report influences in the reframing and the constitution of the image itself, it is also reinterpreted and made from that image of themself new meaning. In this perspective, the driving strength that propels the subject to this constant reinterpretation of the image itself is grounded in the desire to break paradigms and improve on the use of digital technologies. Thus, the formation of technological habitus depends less generational factor and more social capital, cultural and economic teacher. So whether or not presenting a geek ethos, the postmodern teacher who took a praxis mediated by pedagogical digital artifacts is, above all, curious and this insignia is revealed in the desire to learn and improve themselves constantly.